Anticipatory Balance in Athletes Cerebral Palsy After 6-Month Intervention of Proprioceptive Neuromuscular Facilitation Stretching Techniques - Martino, Nieko Caesar Agung; Subadi, Imam; Satyawati, Rwahita; Indriani, Diah ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: The effect of Proprioceptive Neuromuscular Facilitation (PNF) stretching, in addition to standard stretching, improves anticipatory balance in athletes with Cerebral Palsy (CP). We aimed to analyze the effects of PNF stretching to standard training over 4 weeks on anticipatory balance in Cerebral Palsy athletes at 6-month post-intervention evaluation. Methods: The subjects of this study are 24 athletes with Cerebral Palsy at the Indonesian National Paralympic Committee (NPC) training facility. Subjects divided into the treatment group (n = 12) received standard stretching exercises along with PNF stretching, and the control group (n = 12) performed only standard stretching exercises. Both groups received intervention 3 times per week for 4 weeks and evaluation 6 months post-intervention. Y balance tests (YBT) were measured in three directions: anterior (A), posterolateral (PL), and posteromedial (PM), pre- and post-intervention.Results: There was significant improvement of YBT in the treatment group after 4 weeks of intervention. For the right and left limbs, marked increases were observed in all directions (p < 0.05). No significant improvements in YBT were observed at 6 months post-intervention in all directions (p > 0.05).Conclusions: Significant improvements in the Y Balance Test were observed after 4 weeks, but no differences between the two groups at the 6-month evaluation. These findings suggest that while short-term gains in dynamic stability are achievable with PNF, sustained benefits require ongoing reinforcement to maintain neuromuscular adaptations over time.